The performance demands and technical determinants for tackle and ruck success during the pool and knockout stages of the men's international world rugby sevens series - de Klerk, F.; Jones, B.; Maree, W.; Hendricks, S. (European Journal of Sport Science, 2025)
The purpose of this study was to compare tackle and ruck frequencies between pool and knockout matches during the Men's International World Rugby Sevens Series and also determine which technical determinants increase the likelihood of tackle success within each stage of the tournament. Video analysis of all matches during the 2018/2019 International Men's Rugby Sevens World Series was conducted (n = 449 matches). This equated to 21226 tackle contact events and 6345 rucks events. Each tackle event was further coded for tackle descriptors (type of tackle, direction of contact and point of body contact) and tackle outcomes (successful and unsuccessful). No differences were found between the mean tackles per match of pool and knockout stages (pool 47.5, 95% CI 46.5-48.6 vs. knockout 46.9, 95% CI 45.7-48.0). There was a significant difference (p < 0.001) in mean rucks per match between pool and knockout stages (pool 14.8, 95% CI 14.2-15.4 vs. knockout 13.3, 95% CI 12.7-13.9). In conclusion, tackle frequencies per match remained consistent across the series and between the different competition stages and match halves. Ruck frequencies on the other hand decreased from the first tournament to latter parts of the series, and fewer rucks were observed in the knockout stage of the tournaments. The frequency and higher likelihood of tackle success for arm tackles in Sevens highlights a unique demand of Sevens, which strengthens the argument for Sevens-specific tackle training and coaching.